Transformation of Traditional Teaching Methods in the Context of Karl Popper’s Conception of Education (Acta Education, 2024)
This article explores the impact of Karl Popper's educational philosophy on traditional teaching practices. By analyzing the core principles of his theory, the author evaluates the strengths and weaknesses of conventional teaching methods in light of contemporary educational standards. Following this, the author proposes specific strategies for adapting traditional methods to align with Popper's ideals, such as using research projects method, project method and case-study. The author provides practical suggestions for implementing new approaches to teaching and organizing the educational process, drawing on Popper's ideas.